Fungal burn wound infection caused by Fusarium dimerum: A case series on a rare etiology. (October 2021) - Khalid, Subaina Naeem; Rizwan, Nousheen; Khan, Zeest Ali; Najam, Ali; Khan, Amin Moazzam; Almas, Talal; Khedro, Tarek; Nagarajan, Vikneswaran Raj; Alshamlan, Abdulaziz; Gronfula, Amin; Alshehri, Rahaf
Abstract: Introduction: Fusarium dimerum is a filamentous mold associated with poor outcomes in immunocompromised hosts and burn victims. It can be acquired via inhalation or through skin dehiscence. Methods: Our work presents a Case series of 8 patients from ages 3–57 years who were admitted with multiple burn wounds over the past 6 months. After initial stabilization measures, they all underwent debridement for the lesions after negative initial fungal cultures. The 44-year-old male was the first patient to develop punched-out eruptions on burn areas 7 days after admission; all the other patients experienced similar lesions during the next 6 days. Tissue cultures of the lesions exhibited Fusarium dimerum growth. The patients were managed accordingly with amphotericin B or voriconazoles. All the patients recovered except the 11-year-old boy, who expired on day 9 due to ARDS and sepsis complications. Outcomes: Infection with Fusarium dimerum carries a high risk of dissemination in burn infections. Hence, appropriate screening should be carried out via histologic and mycologic diagnostics early in the disease course. Conclusion: Considering the sparse literature that is available regarding Fusarium infection in burn victims, this study aims to improve the knowledge surrounding different facets of this disease including its epidemiology, diagnosis, management, and the need to maintain high suspicion of this fungal disease in burn patients. Highlights: Fusarium dimerum is a filamentous mold associated with poor outcomes in immunocompromised hosts and burn victims. It can be acquired via inhalation or through skin dehiscence. Our work presents a Case series of 8 patients from ages 3–57 years who were admitted with multiple burn wounds over the past 6 months. After initial stabilization measures, they all underwent debridement for the lesions after negative initial fungal cultures. Infection with Fusarium dimerum carries a high risk of dissemination in burn infections. Hence, appropriate screening should be carried out via histologic and mycologic diagnostics early in the disease course.